EVALUATION OF ANXIOLYTIC ACTIVITY OF AERIAL PARTS OF Sarcostigma kleinii Wight. & Arn. - Sabu, Naina Sara (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objectives: The present study was designed to evaluate the anxiolytic effect of Sarcostigma kleinii through the ethanolic extract of its aerial parts. Methods: The study duration was five days and Swiss albino mice were subjected to dosage of 400mg/kg. The anxiolytic effect of the ethanolic extract was evaluated in light and dark, elevated plus maze, and stair case models. Finally neurotransmitters such as serotonin (5HT) and GABA was estimated in mice brain. Results: The ethanolic extract was effective in inducing anxiolytic effects when compared with control group. Decreased serotonin (5HT) and increased level of GABA was observed in ethanolic extract, when compared with control group. Conclusion: The alkaloids, flavonoids and other chemical constituents are speculated to account for the observed pharmacological effects of the plant extract in the experimental animal paradigms used. These findings suggest that the ethanolic extract from the aerial parts of Sarcostigma kleinii exhibits significant anxiolytic activity. Keywords: Sarcostigma kleinii, Anxiolytic activity, Gamma-aminobutyric acid, Serotonin.